Analisis Perancangan Knowledge Management System Pada PLN Unit Pelaksana Proyek JBB 1 Lontar dengan Model Socialization, Externalization, Combination, Internalization - Amanda Khoirunisa; Ahmad Juang Pratama (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
There are several agencies that have not utilized information technology as a medium to increase productivity and learning for human resources. One of them is at PT. PLN (Persero) UIP JBB – UPP JBB 1 Lontar there are obstacles in collecting constraints that arise in the construction sector. The collection of obstacles is still done manually using spreadsheets, and sometimes HR is confused about which obstacles should be discussed at weekly meetings, and the distribution of information related to obstacles is not yet comprehensive to every employee. One solution in processing and providing information systems is in the form of a website. Based on these problems, this research uses a Knowledge Management System (KMS) to collect, store, process and disseminate knowledge so that the information obtained is more accurate and efficient. Assisted by the Socialization, Externalization, Combination, Internalization (SECI) model which can be used in building an application is the basis for creating knowledge and transferring theory. Based on the analysis that has been carried out, it can be concluded that KMS can be applied as an information system to manage any obstacle data that arises in the construction sector at UPP JBB 1 Lontar. There are features required on a website based on the SECI model, including a column for proposing follow-up on constraints, a constraint data document, and an urgent risk column in the Externalization process, a menu feature for downloading constraint data in the Combination process, as well as a constraint and proposal data feature in the Internalization process.Keywords – Knowledge Management System (KMS), SECI Model, Use Case Diagram, Website